Allelic variation in the indoleacetic acid-lysine synthase gene of the bacterial pathogen Pseudomonas savastanoi and its role in auxin production - Pintado, Adrián; Domínguez-Cerván, Hilario; Pastor, Victoria; Vincent, Marissa; Lee, Soon Goo; Flors, Víctor; Ramos, Cayo (Frontiers in Plant Science, 2023)
Indole-3-acetic acid (IAA) production is a pathogenicity/virulence factor in the Pseudomonas syringae complex, including Pseudomonas savastanoi. P. savastanoi pathovars (pvs.) genomes contain the iaaL gene, encoding an enzyme that catalyzes the biosynthesis of the less biologically active compound 3-indole-acetyl-ε-L–lysine (IAA–Lys). Previous studies have reported the identification of IAA–Lys in culture filtrates of P. savastanoi strains isolated from oleander (pv. nerii), but the conversion of IAA into a conjugate was not detectable in olive strains (pv. savastanoi). In this paper, we show the distribution of iaaL alleles in all available P. savastanoi genomes of strains isolated from woody hosts. Most strains encode two different paralogs, except for those isolated from broom (pv. retacarpa), which contain a single allele. In addition to the three previously reported iaaL alleles (iaaLPsv, iaaLPsn and iaaLPto), we identified iaaLPsf, an exclusive allele of strains isolated from ash (pv. fraxini). We also found that the production of IAA–Lys in P. savastanoi pv. savastanoi and pv. nerii depends on a functional iaaLPsn allele, whereas in pv. fraxini depends on iaaLPsf. The production of IAA–Lys was detected in cultures of an olive strain heterologously expressing IaaLPsn-1, IaaLPsf-1 and IaaLPsf-3, but not when expressing IaaLPsv-1. In addition, Arabidopsis seedlings treated with the strains overproducing the conjugate, and thus reducing the free IAA content, alleviated the root elongation inhibitory effect of IAA. IAA–Lys synthase activity assays with purified allozymes confirmed the functionality and specificity of lysine as a substrate of IaaLPsn-1 and IaaLPsf-3, with IaaLPsf-3 showing the highest catalytic efficiency for both substrates. The IAA–Lys synthase activity of IaaLPsn-1 was abolished by the insertion of two additional tyrosine residues encoded in the inactive allozyme IaaLPsv-1. These results highlight the relevance of allelic variation in a phytohormone-related gene for the modulation of auxin production in a bacterial phytopathogen.